PELATIHAN KADER POSYANDU LANSIA DAN SENAM LANSIA DI DESA GUWANG KECAMATAN SUKAWATI KABUPATEN GIANYAR - Ni Made Sri Muryani; Komang Agus Jerry Widyanata; I Wayan Warditha (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2019)
Aging is a process of disappearing slowly the ability of the network to repair, replace itself and maintain its normal structure and function. In an effort to improve the health of the elderly effectively, it needs to be supported by adequate human resource skills where one of them is an elderly Posyandu cadre. After training for elderly cadres and posyandu and elderly gymnastics, it is expected that the performance of the elderly posyandu cadres can be optimized so that they can provide better health services to the elderly. Method: This activity uses the Community Empowering approach with the method of lecturing, discussion and demonstration and this activity is divided into three stages, namely preparation, implementation, and evaluation. Result: The formation of elderly cadres, increasing knowledge of the elderly, elderly posyandu and the implementation of elderly gymnastics. Conclusion: Training of elderly posyandu cadres and elderly gymnastics has been carried out well in the form of selection of elderly cadres, implementation of elderly posyandu, andelderly gymnastics through the provision of materials and training for elderly posyandu. It is expected that Puskesmas officers will always supervise and evaluate the elderly posyandu activities in Guwang Village, so that the elderly was monitored for their health conditions.